Faktor-faktor yang Mempengaruhi Minat Menabung di Bank Syariah Surakarta - Ipfa Retno Astuti (Entrepreneurship Faculty, Universitas Garut, 2020)
Abstract– This study aims to examine and analyze the effect of religiosity, profit sharing and service on interest in saving at the Surakarta Islamic Bank. The benefits that are expected to increase and provide knowledge related to the influence of religiosity, profit sharing and services on the interest in saving at the Surakarta Islamic Bank, can be used as material for community consideration and Islamic banking management to develop the role of Islamic banking and marketing strategies in Surakarta. The sampling technique was using purposive sampling technique. The population and sample in this study were 71 people who fit the specified criteria. The data were processed using SPSS, the tests carried out included instrument tests, classical assumption tests and multiple linear regression tests. The conclusion in this study is that religiosity has an effect on the interest in saving in Islamic banks in Surakarta. Profit sharing affects the interest in saving in Islamic banks in Surakarta. Services affect the interest in saving at a syariah bank in Surakarta. Abstrak– Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh religiusitas, bagi hasil dan pelayanan terhadap minat menabung di Bank Syariah Surakarta. Manfaat yang diharapkan dapat menambah dan memberikan pengetahuan yang berkaitan dengan pengaruh religiusitas, bagi hasil dan pelayanan terhadap minat menabung di Bank Syariah Surakarta, dapat digunakan sebagai bahan pertimbangan masyarakat dan manajemen perbankan syariah untuk mengembangkan peranan perbankan syariah dan strategi marketing di Kota Surakarta. Teknik pengambilan sampel menggunakan teknik purposive sampling. Populasi dan sampel dalam penelitian ini adalah 71 orang yang sesuai dengan kriteria yang ditentukan. Data diolah menggunakan SPSS , pengujian yang dilakukan meliputi uji instrumen, uji asumsi klasik dan uji regresi linier berganda. Kesimpulan dalam penelitian ini adalah religiusitas berpengaruh terhadap minat menabung di bank syariah surakarta. Bagi hasil berpengaruh terhadap minat menabung di bank syariah surakarta. Pelayanan berpengaruh terhadap minat menabung di bank syariah surakarta.